The Influence Of Culture And Attitude On Students’ Lms Acceptance In Learning Mathematics At The University Of Ha’il In Saudi Arabia - Fahad A, Alshammari Khaled (2022)
In the past few decades, information and communication technology (ICT) has grown rapidly, promoting the use of e-learning resources such as learning management system (LMS), which is now a requirement in Saudi Arabia. LMS was adopted to increase learning experience, prepare students by teaching them technology-related skills and enabling them to become competitive, and reducing time and space use in educational processes. The theoretical basis for researching variables affecting the usage of the LMS is focused on Unified Theory of Acceptance and Use of Technology (UTAUT). On the basis of these hypotheses, it is assumed that the model constructs will improve the behavioural intention of the students to use LMS at an incremental level in studying mathematics. Only three cultural dimensions showed no significant effect on LMS usage by the students, which may be attributed to the complexities of Saudi Arabian society. In this study a questionnaire was used to explore the perceptions of students regarding the variables of the study. The data were collected and evaluated using the Statistical Package for the Social Sciences (SPSS). In fact, focused on analytical principles of the social sciences, data analysis includes three major steps: preparing and arranging data for review (data preparation), explaining data (descriptive statistics), and evaluating theories and models (inferential statistics). Measurement model is a component of the route model that involves structures (latent variables) and their relationships with their markers (items), defined in PLS–SEM as the outer model. Researchers choose the evaluation tool for the calculation process depending on the type of structures in the model, whether predictive or formative tests. The research hypotheses that success expectation, commitment expectation, social influence, attitude and culture of the students have a significant positive effect on the behavioral intention of the undergraduate students towards the use of the LMS in learning mathematics at UOH in Saudi Arabia. In addition, behavioral intention is strongly linked to the real use of the LMS by UOH undergraduate students in learning mathematics. The current findings illustrated that although several studies showed a positive relationship between the mindset of students and their behavioural intention towards the use of the LMS.